Urinary ferritin and cystatin C concentrations at different stages of kidney disease in leishmaniotic dogs. (April 2015) - García-Martínez, J.D.; Martinez-Subiela, S.; Tvarijonaviciute, A.; Caldin, M.; Ceron, J.J.
Highlights: Our aim is to evaluate urinary ferritin and cystatin C concentrations in dogs with several stages of chronic kidney disease. We use dogs naturally infected with leishmania sp . Ferritin and cystatin C concentrations were increased in the urine of dogs with renal damage. Urinary ferritin concentration increased in dogs with proteinuria but without hypercreatinemia. Urinary ferritin is a renal biomarker earlier than creatinemia. Abstract: Traditional analytes do not detect early renal disease; therefore there is a need to find new early markers of chronic kidney disease (CKD) in dogs to avoid the progression to irreversible renal damage. Our objective was to evaluate the presence of ferritin and cystatin C in urine of dogs with CKD and to relate their concentrations with the severity of the disease. Samples obtained from dogs naturally infected with Leishmania infantum were classified into four groups on the basis of the results of urinary protein/creatinine ratio and serum creatinine. This study shows that ferritin and cystatin C concentrations were increased in the urine of dogs with renal damage. Cystatin C value in urine only increased in severe stages of CKD with serum creatinine values >1.4 mg/dL, while the urinary ferritin concentration increased in dogs with proteinuria and serum creatinine <1.4 mg/dL, being, therefore, a renal biomarker earlier than creatinemia.